Effects of prolonged use of virtual reality smartphone-based head-mounted display on visual parameters: a randomised controlled trial - Hyeon Jeong Yoon (Nature Portfolio, 2021)
Abstract We investigated the effects of using a virtual reality smartphone-based head-mounted display (VR SHMD) device for 2 h on visual parameters. Fifty-eight healthy volunteers were recruited. The participants played games using VR SHMD or smartphones for 2 h on different days. Visual parameters including refraction, accommodation, convergence, stereopsis, and ocular alignment and measured choroidal thickness before and after the use of VR SHMD or smartphones were investigated. Subjective symptoms were assessed using questionnaires. We analyzed the differences in visual parameters before and after the use of VR SHMD or smartphones and correlations between baseline visual parameters and those after the use of the devices. Significant changes were observed in near-point convergence and accommodation, exophoric deviation, stereopsis, and accommodative lag after the use of VR SHMD but not after that of smartphones. The subjective discomfort associated with dry eye and neurologic symptoms were more severe in the VR group than in the smartphone group. There were no significant changes in refraction and choroidal thickness after the use of either of the two devices. The poorer the participants’ accommodation and convergence ability the greater the resistance to changes in these visual parameters, and participants with a large exophoria were more prone to worsening of exophoria than those with a small exophoria.